RANCANG BANGUN PROTOTIPE ALAT ANGKUT LOGAM BERBASIS ARDUINO UNO - Bima Franata Sagita; Eka Purwa Laksana (MAESTRO, 2021)
There are still many uses of transportation means to move goods manually, even though there are many shortcomings in it. One of the drawbacks is that the push button must be continuously pressed by the operator until it reaches the desired place, this of course will take a lot of time and full concentration from the operator himself. In this final project, a prototype design of an Arduino Uno based automatic metal conveyance is designed to be able to move goods automatically. The design of the prototype for automatic metal conveyance based on Arduino Uno uses the infrared avoid obstacle sensor as object detection, DC motor as the main driver for moving goods, and uses LD micro software. The working method of the prototype design for this automatic metal transportation device based on Arduino Uno is when the automatic switch is turned on, the DC motor 1 works to transport the drum containing metal vertically (up and down) to the infrared avoid obstacle sensor, then the DC motor 2 will work horizontally (forward -back) heading to tubs 1, 2, and 3 to move metal automatically. Based on the test results that have been carried out, the design of the prototype automatic transportation tool based on Arduino Uno has a difference in the duration of time to transport metal with different loads, namely, if without load the time needed to transport goods is 94 seconds, with a load of 36.5 grams is 101 seconds. , and with a load of 111.1 is 103 seconds, with a time difference from no load to a load of 111.1 grams is 9 seconds.